CONCERNS OF ABO INCOMPATIBLE AND CROSSMATCH-POSITIVE POTENTIAL DONORS AND RECIPIENTS ABOUT PARTICIPATING IN KIDNEY EXCHANGES - Rodrigue, James R. (Clin Transplant, 2015)
Kidney paired exchanges (KPE) have increased, yet are still underutilized. This study aimed to develop tools for assessing KPE concerns, identify predictors of KPE concerns, and describe common KPE concerns among potential living donors (LDs) and intended recipients. Incompatible former potential LDs (n=135) and intended recipients (n=83) retrospectively completed questionnaires to assess KPE concerns. Healthcare system distrust also was assessed. A minority (n=48 or 36.5% of potential LDs; n=25 or 30.1% of intended recipients) had pursued KPE participation. Of those who pursued KPE participation, 11 (22.9%) and 6 (24.0%) completed KPE donation or transplantation, respectively. The questionnaires for potential LDs and recipients showed good internal consistency and preliminary convergent validity. LDs and patients less willing to pursue KPE reported more KPE concerns. Common KPE concerns for both potential LDs and recipients were related to perceived distrust/inequity and inconvenience/cost. Multivariate predictors of more KPE concerns were: male gender (t=4.5, p<0.001) and more health care system distrust (t=2.5, p=0.01) for potential LDs; black race (t=2.1, p=0.04) and more healthcare system distrust (t=2.3, p=0.03) for intended recipients. These findings underscore the importance of addressing concerns potential LDs and patients have about KPE if the true potential of KPE is to be realized.